Long-term haemodialysis and thyroid function. Issue 6054 (15th January 1977) - Dandona, P; Newton, D; Platts, M M
Abstract : Several indices of thyroid function were assessed in 74 patients with chronic renal failure. Sixty patients had undergone haemodialysis for varying periods. Within the first six months of haemodialysis treatment protein-bound iodine and total thyroxine (T4) levels rose, but after this T4 levels and the free thyroxine index fell progressively. Three out of the 12 patients who had undergone haemodialysis for longer than three years had subnormal T4 and supranormal thyrotrophin concentrations and a subnormal response to thyrotrophin stimulation. Lon-term haemodialysis may be a cause of biochemical hypothyroidism.